The Results of Testing Several Potato Varieties (Solanum tuberosum L.) Under The Stands of Immature Coffee Plants - Benni Satria (JERAMI : Indonesian Journal of Crop Science, 2020)
Potatoes have the potential to be developed as a source of carbohydrates in supporting food diversification programs. Reduced potatoes production has resulted from a decrease in the land area for potato cultivation. The effort that can be made to increase land productivity is through multiple cropping systems such as intercropping, intermittent intercropping, streak planting, annual intercropping, and agroforestry. It is necessary to use idle land under plantation stands that have not been optimized, in increasing productivity and efficiency of agricultural production systems. This study aims to get the varieties that have the best growth and yields planted under immature coffee stands. This research applies a Single Factorial Experiment in Completely Random Design, where the factor is four levels of potato varieties, Granola (V1), Bliss (V2), Kentang Merah (V3) and Batang Hitam (V4). Observations made include plant height, number of leaves, leaf length, leaf width, tuber length, tuber diameter, weight per tuber, number of tubers/plat, and total tuber by grade tubers (Small, Medium, Large, Very large). Based on the analysis variance of each observation variable shows, there is an effect of the variable observation except the width of the leaves. Granola provides the best response to the growth and yield of potato plants